Discharge Characteristics of Large-Area High-Power RF Ion Source for Positive and Negative Neutral Beam Injectors*supported by the Ministry of Science, ICT and Future Planning of the Republic of Korea under the ITER Technology R&D Program, and National R&D Program Through the National Research Foundation of Korea (NRF) Funded by the Ministry of Science, ICT & Future Planning (NRF-2014M1A7A1A03045372). (December 2016) - Chang, Doo-Hee; Jeong, Seung Ho; Park, Min; Kim, Tae-Seong; Jung, Bong-Ki; Lee, Kwang Won; In, Sang Ryul
Abstract: A large-area high-power radio-frequency (RF) driven ion source was developed for positive and negative neutral beam injectors at the Korea Atomic Energy Research Institute (KAERI). The RF ion source consists of a driver region, including a helical antenna and a discharge chamber, and an expansion region. RF power can be transferred at up to 10 kW with a fixed frequency of 2 MHz through an optimized RF matching system. An actively water-cooled Faraday shield is located inside the driver region of the ion source for the stable and steady-state operations of high-power RF discharge. Plasma ignition of the ion source is initiated by the injection of argon-gas without a starter-filament heating, and the argon-gas is then slowly exchanged by the injection of hydrogen-gas to produce pure hydrogen plasmas. The uniformities of the plasma parameter, such as a plasma density and an electron temperature, are measured at the lowest area of the driver region using two RF-compensated electrostatic probes along the direction of the short-and long-dimensions of the driver region. The plasma parameters will be compared with those obtained at the lowest area of the expansion bucket to analyze the plasma expansion properties from the driver region to the expansion region.